Transcranial Magnetic Stimulation with Intermittent Theta Burst Stimulation Alters Corticospinal Output in Patients with Chronic Incomplete Spinal Cord Injury - Fassett, Hunter J.; Turco, Claudia V.; El-Sayes, Jenin; Lulic, Tea; Baker, Steve; Richardson, Brian; Nelson, Aimee J. (Frontiers in Neurology, 2017)
Intermittent theta burst stimulation (iTBS) is intended primarily to alter corticospinal excitability, creating an attractive opportunity to alter neural output following incomplete spinal cord injury (SCI). This study is the first to assess the effects of iTBS in SCI. Eight individuals with chronic incomplete SCI were studied. Sham or real iTBS was delivered (to each participant) over primary motor and somatosensory cortices in separate sessions. Motor evoked potential (MEP) recruitment curves were obtained from the flexor carpi radialis (FCR) muscle before and after iTBS. Results indicate similar responses for iTBS to both motor and somatosensory cortex and reduced MEPs in 56.25% and increased MEPs in 25% of instances. Sham stimulation exceeded real iTBS effects in the remaining 18.25%. It is our opinion that observing short-term neuroplasticity in corticospinal output in chronic SCI is an important advance and should be tested in future studies as an opportunity to improve function in this population. We emphasize the need to re-consider the importance of the direction of MEP change following a single session of iTBS since the relationship between MEP direction and motor function is unknown and, multiple sessions of iTBS may yield very different directional results. Further, we highlight the importance of including sham control in the experimental design. The fundamental point from this pilot research is that a single session of iTBS is often capable of creating short-term change in SCI. Future sham-controlled randomized trials may consider repeat iTBS sessions to promote longer-term changes in corticospinal excitability.